(untitled) (Teología, 2018)
This paper shows the concordance among the mysticism, the experience and the phenomenology of donation. In the relationship of man to God there is the possibility of focusing on the distance of concept and rational understanding, or, on the depth of the concrete experience of love. It is precisely here where the gift of God acquires all its pre-eminence, provided that it becomes a mystical experience of gratuitousness, in which man gives up to rely on his own forces and God’s mental representations, to open himself to receive the divine gift as revealed phenomenon. At first, the linguistic limits of the mystical experience are approached, which exceeds any rational knowledge; later, the mystical itinerary is examined, as a divine kenosis that impacts the life of man and transforms it; finally, a synthesis of the theological turn of phenomenology is made, highlighting the donation as a scenario of the revelation of God in man, who after making the gratuitous experience of God’s love as a givenness, feels consequently driven to transmit it to others in witness quality.